Implementation of Merdeka Curriculum in Improving the Quality of Senior High School - Sinta Nur Kamila; Abu Hasan Agus RM (Universitas Majalengka, 2023)
This study aims to determine the implementation of an merdeka curriculum: quality improvement efforts in educational institutions. This research was conducted at SMAN 2 Jember with a qualitative approach through case study research. Data were obtained from observation, interviews, and documentation studies. Informants in the study were the principal, deputy head of curriculum, teachers, and students. In the process of analyzing data, the researcher collects data, reduces data, presents data, and concludes findings. The results of the study show the success of the implementation of the merdeka curriculum in improving the quality of schools through the learning process carried out, namely by preparations including the need to get information about the merdeka curriculum by preparing teachers how they understand what the merdeka curriculum means; teachers take part in online and offline workshops held by the government and the education office besides that the school also conducts its workshops merdekaly by bringing in resource persons related to the merdeka curriculum so that it becomes an excellent contribution to the sustainability and improvement of the quality of education and achieves educational goals that require students to enrich literacy to get to the future era of globalization.